Penerapan Terapi Musik untuk Menurunkan Gejala Negatif pada Penderita Schizophrenia di Panti Sosial X - Kamardi, Jonas Danny Margan; Satiadarma, Monty P.; Suryadi, Denrich (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2017)
As one of the social problems, schizophrenia has been noticed by theIndonesian government through Social Department. The constant increasing number of schizophrenics in Jakarta induces limitation of anti-psychotic drugs use in social institutions related to issues of financial support. Although the positive symptoms of the Schizophrenics can only be handled with pharmacotherapy, schizophrenic’s well-being have the chance to be improved by reducing the negative symptoms. The use of creative therapies such as music therapy as a clinical intervention are potential to reduce negative symptoms in individual or group settings. Music therapy can be applied in a passive way, such as listening to music, and active way, which is singing and playing musical instruments. Positive and Negative Syndrome Scale (PANSS) was used to evaluate the negative symptoms of the participants. Systematic approach on learning to sing was implemented as the therapeutic approach on the participants. The sessions were conducted as many as 8 Sessions. The result indicates that music therapy by the way of singing can reduce the negative symptoms of the schizophrenic patients.Keywords: schizophrenia, negative symptoms, music therapy, positive and negative syndrome scale (PANSS).